Posteroventrolateral pallidotomy through implanted DBS electrodes monitored by recording local field potentials. (2nd November 2015) - Franzini, Angelo; Cordella, Roberto; Penner, Federica; Rosa, Manuela; Messina, Giuseppe; Rizzi, Michele; Nardocci, Nardo; Priori, Alberto
Abstract : This paper describes the use of globus pallidus internus (Gpi) local field potentials recorded through pre-implanted deep brain stimulation (DBS) electrodes on a patient affected by generalized dystonia. The recordings were made both before and after radiofrequency-induced posteroventrolateral bilateral stereotactic pallidotomy. LFP patterns and macroelectrode impedances were modified after the pallidotomy, along with the improvement of dystonic symptoms. After implantation, the DBS electrodes were used for subsequent bedside pallidotomies that were required by the evolution and/or persistence of symptoms. In our hands, LFPs were safe and effective in monitoring pallidotomy performed through DBS electrodes.